2017
DOI: 10.1016/j.puhe.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

After 50 years and 200 papers, what can the Midspan cohort studies tell us about our mortality?

Abstract: These studies highlight the cumulative effect of adverse exposures throughout life, the complex interplay between social circumstances, culture and individual capabilities, and the damaging effects of smoking, air pollution, alcohol and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The prevalence of smoking in this study is significantly lower than recently released national data on men from the South African Demographic and Health survey in which it was reported that 36% of black adult men smoke tobacco products, but similar in black women who reported a 3% prevalence of tobacco smoking. Although associated with a lower BMI in this study, smoking is a major risk factor for premature mortality [27], NCDs and cardiovascular disease [28], independent of BMI, and is therefore a lifestyle behaviour that must be avoided. Further, smoking has been associated with greater central adiposity [29].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smoking in this study is significantly lower than recently released national data on men from the South African Demographic and Health survey in which it was reported that 36% of black adult men smoke tobacco products, but similar in black women who reported a 3% prevalence of tobacco smoking. Although associated with a lower BMI in this study, smoking is a major risk factor for premature mortality [27], NCDs and cardiovascular disease [28], independent of BMI, and is therefore a lifestyle behaviour that must be avoided. Further, smoking has been associated with greater central adiposity [29].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in educational level between the groups can possible skew the results, since level of education may have an influence on psychological stress [33, 34], but performing unadjusted and adjusted ANOVA educational level did not influence the stress level (GHQ, IES and EPDS), except in adjusted analysis for IES arousal. See S1 Table.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence points to material disadvantage and air pollution in early years and culturally mediated behaviours including smoking, drinking alcohol and unhealthy eating, which may be less prevalent in some ethnic minority groups 21. The possibility that people who migrate to another country, particularly over long distances, may be intrinsically healthier on average than those they leave behind (the healthy migrant effect) may also play a part 22.…”
Section: Discussionmentioning
confidence: 99%